An ultra-long life, high-performance, flexible Li–CO2 battery based on multifunctional carbon electrocatalysts. (May 2020) - Song, Li; Hu, Chuangang; Xiao, Ying; He, Jianping; Lin, Yi; Connell, John W.; Dai, Liming
Abstract: Integrating CO2 utilization and renewable energy delivery/storage, the rechargeable Li–CO2 battery has been considered as a promising candidate for next-generation secondary batteries. However, high-performance catalyst(s) for efficient formation and decomposition of the discharge product, Li2 CO3, are an imperative part of a Li–CO2 battery. The development of flexible Li–CO2 batteries extends their applications into compliant and wearable devices/systems, but at the same time imposes a big challenge for battery fabrication and lifetime enhancement. In this study, a rechargeable quasi-solidus flexible Li–CO2 battery was designed and fabricated using highly active N, S-doped carbon nanotubes (N, S-doped CNTs) as the cathode catalyst, and a smart polymer gel as the flexible electrolyte. This newly-developed flexible Li–CO2 battery exhibited a capacity as high as 23560 mAh g −1 based on the catalyst mass and an ultra-long lifetime of up to 538 cycles with excellent mechanical flexibility. This work provides a platform for the design and development of high-performance flexible Li–CO2 batteries from low-cost, earth-abundant, carbon-based multifunctional cathode catalysts. Graphical abstract: An ultra-long-life, high-performance quasi-solidus flexible Li–CO2 battery was successfully fabricated by employing a highly active N, S-doped carbon nanotube cathode, a smart gel electrolyte, and a rationally designed robust electrode configuration. This newly-developed flexible Li–CO2 battery shows great promise in flexible electronic devices as an attractive power source while utilization of CO2 . Image 1 Highlights: Highly-active N, S-doped carbon bifunctional metal-free catalysts for CO2  reduction and evolution were developed. The rationally-designed N, S-doped CNTs were used as the cathode catalyst for flexible Li-CO2  batteries. The flexible Li-CO2  battery exhibited a capacity and lifetime of up to 23560 mAh g -1  and 538 cycles, respectively. Mechanistic understanding was obtained to provide a guidance for the development of new flexible Li-CO2  batteries.